2015
DOI: 10.3892/ijo.2015.3017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of RPS5 gene expression modulates the initiation of commitment of MEL cells to erythroid maturation: Implications in understanding ribosomopathies

Abstract: Impairment of ribosome biogenesis contributes to the molecular pathophysiology of ribosomopathies by deregulating cell-lineage specific proliferation, differentiation and apoptosis decisions of haematopoietic progenitor cells. Here, using pro-erythroblast-like murine erythroleukemia (MEL) cells, a model system of erythroid maturation, we aimed to investigate whether genetic manipulation of RPS5 expression affects the capacity of cells to grow and differentiate in culture. Parental MEL cells stably transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
16
0
2
Order By: Relevance
“…Studies over the past years have shown that there is stringent and precise regulation of ribosome levels and function during erythropoiesis. This is evident under conditions of mild ribosome dysfunction, as it occurs in a group of disorders termed ribosomopathies [14,44,45]. The latter are caused by heterozygous mutations in ribosomal proteins and associate with highly specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies over the past years have shown that there is stringent and precise regulation of ribosome levels and function during erythropoiesis. This is evident under conditions of mild ribosome dysfunction, as it occurs in a group of disorders termed ribosomopathies [14,44,45]. The latter are caused by heterozygous mutations in ribosomal proteins and associate with highly specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As with other cancer types, erythroleukemias show an imbalance in favor of hyperproliferative phenotypes over differentiation. However, extensive work in established cell line erythroleukemia models (especially murine erythroleukemia, MEL, cells) has shown that the leukemic phenotype can be reversed in vitro by reintroducing the cells into the path of differentiation [10][11][12][13][14][15][16]. Differentiation is initiated after treatment with chemical inducers (such as hexamethylene bisacetamide, HMBA) and involves an extensive yet precisely orchestrated gene expression program [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…The increasingly accumulated evidence suggests that ribosomal proteins has extra-ribosomal functions associated with cell differentiation, apoptosis, regulation of signal pathway, and DNA repair (LindstrÖm, 2009;Warner and Mcintosh, 2009). RPS5 was also found to participate in extra-ribosomal activities such as cell differentiation (Matragkou et al, 2008;Vizirianakis et al, 2015), intracellular trafficking (Matragkou et al, 2009), and hepatic fibrosis (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse erythroleukemic (MEL) cells (clone 745-PC–4) were derived from the MEL 745 cell line, originally isolated by Friend et al [ 25 ] and were maintained and induced to differentiate with 5mM of HMBA (N,N-Hexamethylene-bis- acetamide, Sigma) as previously described [ 26 ]. Cell culture density and differentiation (hemoglobin production) were assessed as previously described [ 26 ].…”
Section: Methodsmentioning
confidence: 99%